Bisphenol A and its analogs bisphenol B, bisphenol F, and bisphenol S: Comparative in vitro and in vivo studies on the sperms and testicular tissues of rats. (October 2018) - Ullah, Asad; Pirzada, Madeeha; Jahan, Sarwat; Ullah, Hizb; Shaheen, Ghazala; Rehman, Humaira; Siddiqui, Mariyam Fatima; Butt, Maisra Azhar
Abstract: Bisphenol A (BPA) is used as the main component of many consumer products such as infant's feeding bottles, coatings of beverages, and food cans. BPA can migrate into the environment, and it has been detected in the saliva, blood, and food. BPA leakage from many consumer products resulted in a ban on its use in many countries where alternatives to BPA were introduced into the market. BPA alternatives such as bisphenol B (BPB), bisphenol F (BPF), and bisphenol S (BPS) have a similar chemical structure and binding ability for estrogen receptor (ER), which shows toxicological effects in animals. In the present study, comparative effects of exposure to BPA and its analogs BPB, BPF, and BPS on testosterone concentration in the rat testis were evaluated by in vitro and in vivo approaches in which oxidative stress markers and antioxidant enzyme activities in reproductive tissues were determined. In the in vivo study, male rats were exposed to different concentrations of BPA and its analogs BPB, BPF, and BPS (5, 25, and 50 mg/kg/day) for 28 days. In the in vitro exposure study, antioxidant enzyme activities and oxidative stress markers were induced in the testes, whereas testosterone production was reduced. In the in vivo exposure study, we observed that antioxidant enzyme activities and protein content were reduced, whereas reactive oxygen species and lipid profile were increased in the treated groups compared to the control group. The present comparative study on BPA and its analogs, namely, BPB, BPF, and BPS suggests the toxic effect of these chemicals on the testes and spermatogenesis, and we also observed that these chemicals induce oxidative stress in the reproductive tissues of male rats. Highlights: Comparative toxicity effects of BPA and its analogs BPB, BPF, and BPS on the reproductive system of male rats. In vitro study was conducted with cultured cells of the rat testicular tissue, BPA, BPB, BPF, and BPS induced oxidative stress. BPA and its analogs BPB, BPF, and BPS reduced plasma and intratesticular testosterone concentrations.